Social networks as social capital for eco-tourism in Malaysia : a preliminary sociological study of the Langkawi Geopark - Chan, Geraldine K.L. (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
Theoretically and empirically, the transformation of social networks into social capital is made possible by the interplay between social relationships, social interactions, shared network values, some similarities, network norms, network sanctions and benefits primarily at the informal level between social actors who are connected and collectively involved in the tourism activities. In other words, the networks based on shared values and some similarities as well as normative principles of reciprocity and mutuality will become a form of capital to the actors concerned if their networks while in operation during eco-tourism activities generate monetary and non-monetary benefits for them. Through some empirical findings obtained from a preliminary social network analysis of particular social actors who have been and still are actively and collectively involved in eco-tourism activities in two villages in Langkawi, this study examines the hypothesis that social networks play an important role in the development and success of eco-tourism in Malaysia in the form of social capital. The case examined was Langkawi archipelago of islands in Kedah, a northern state in Peninsular Malaysia where tourism, particularly ecotourism, is the key driver of Langkawi’s socio-economic development, more so after it was declared a geopark in 2007 by Global Geopark Networks (GGN), an initiative under UNESCO. The empirical findings demonstrate that the hypothesis is largely substantiated in the case of Langkawi, that is, the significance of sociological ideas in deriving an alternative, if not better, understanding of the development and success of eco-tourism in Langkawi. The sociological value lies in its emphasis on the “social factor” (i.e. social networks and social capital) as a driver of an economic activity, i.e. eco-tourism activity.